2016
DOI: 10.3164/jcbn.15-132
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurement of skin autofluorescence to evaluate diabetic complications

Abstract: Although the accumulation of advanced glycation end-products (AGEs) of the Maillard reaction in our body is reported to increase with aging and is enhanced by the pathogenesis of lifestyle-related diseases such as diabetes, routine measurement of AGEs is not applied to regular clinical diagnoses due to the lack of conventional and reliable techniques for AGEs analyses. In the present study, a non-invasive AGEs measuring device was developed and the association between skin AGEs and diabetic complications was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…( 23 ) It has been reported that advanced glycation end products, which has a close association with visceral adiposity, is associated with diabetes and diabetes complications. ( 24 ) In addition, abdominal obesity is more related to diabetes than overall obesity. ( 10 , 11 ) Recent studies revealed that a subset of individuals with obesity who have a low burden of adiposity-related metabolic abnormalities compared with individuals with ‘at risk’ obesity, the so-called ‘metabolically healthy obesity’ (MHO) phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…( 23 ) It has been reported that advanced glycation end products, which has a close association with visceral adiposity, is associated with diabetes and diabetes complications. ( 24 ) In addition, abdominal obesity is more related to diabetes than overall obesity. ( 10 , 11 ) Recent studies revealed that a subset of individuals with obesity who have a low burden of adiposity-related metabolic abnormalities compared with individuals with ‘at risk’ obesity, the so-called ‘metabolically healthy obesity’ (MHO) phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The sAF values obtained with the excitation and emission wavelengths of 365 nm and 440 nm, respectively, were used to estimate the levels of AGE accumulation. The obtained sAF levels are correlated positively with the level of the hyperglycemia-associated AGE, Nδ-(5-hydro-5-methyl-4-imidazolone-2-yl)-ornithine (MG-H1) [ 41 ]. The sAF is correlated with collagen-linked fluorescence (CLF) (excitation at 370 nm, emission at 440 nm) that degrades in skin biopsy specimen [ 19 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the intensity of autofluorescence from veins is approximately 1.5-fold higher than that of skin, the influence of the veins is negligible in the measurement of the sAF using the AGEs Sensor, since the fingertips have only capillaries and no veins. Therefore, the fingertip is suitable to avoid non-specific skin fluorescence [ 41 ]. Trained examiners performed all measurements.…”
Section: Methodsmentioning
confidence: 99%
“…In situations of metabolic and oxidative stress, however, accelerated AGE accumulation rates have been described, such as in individuals with cardiovascular disease (CVD) [ 1 , 2 ] and diabetes mellitus (DM) [ 3 , 4 ]. The fairly quick (seconds) and non-invasive assessment of skin autofluorescence (SAF) has been demonstrated to serve as a surrogate marker of tissue accumulation of AGEs [ 5 , 6 ] and recent efforts have been undertaken to develop stratification tools for the clinical assessment of a patient's risk for cardiovascular disease (CVD) [ 7 9 ] and diabetic complications [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%